2020
DOI: 10.3390/cells9010208
|View full text |Cite
|
Sign up to set email alerts
|

Role of Secreted Frizzled-Related Protein 1 in Early Mammary Gland Tumorigenesis and Its Regulation in Breast Microenvironment

Abstract: In mice, the lack of secreted frizzled-related protein 1 (SFRP1) is responsible for mammogenesis and hyperplasia, while, in bovines, its overexpression is associated with post-lactational mammary gland involution. Interestingly, there are no reports dealing with the role of SFRP1 in female involution. However, SFRP1 dysregulation is largely associated with human tumorigenesis in the literature. Indeed, the lack of SFRP1 is associated with both tumor development and patient prognosis. Considering the increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 103 publications
1
11
0
Order By: Relevance
“…The importance of breast adipose tissue in proper breast involution was also indicated in the study on Secreted Frizzled Related Protein 1 (SFRP1). SFRP1 is a known adipokine secreted by adipocytes, and it plays a role in adipogenesis, inflammation and apoptosis [37][38][39] processes that are all of significant importance in breast involution (Figure 1). Furthermore, SFRP1 overexpression was observed in the post-lactation period [40] indicating its role in involution.…”
Section: Adipose Tissue Plasticity During Pregnancy Lactation and Inmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of breast adipose tissue in proper breast involution was also indicated in the study on Secreted Frizzled Related Protein 1 (SFRP1). SFRP1 is a known adipokine secreted by adipocytes, and it plays a role in adipogenesis, inflammation and apoptosis [37][38][39] processes that are all of significant importance in breast involution (Figure 1). Furthermore, SFRP1 overexpression was observed in the post-lactation period [40] indicating its role in involution.…”
Section: Adipose Tissue Plasticity During Pregnancy Lactation and Inmentioning
confidence: 99%
“…The site of involution is enriched with TGFβ, VEGF, TNFα and IL6 [208], which have all been shown to promote cancer, and are also secreted by breast adipose tissue. On the other hand, a review from our group has highlighted that there could be a possible link between the post-lactation overexpression of SFRP1 and complete involution [37], as mice lacking expression of SFRP1 display a breast morphology that is similar to mid-pregnancy mice [41]. This could also suggest a protective role of breast adipose tissue against BC.…”
Section: Involutionmentioning
confidence: 99%
“…SFRP1 seems to be a crucial player in all steps of the age-related lobular involution process [ 8 , 9 , 10 ]. Age-related lobular involution, a physiological breast atrophy described as a natural protective process against breast tumorigenesis [ 11 , 12 , 13 ], is composed of three known phenomena: Inflammation, apoptosis, and adipogenesis [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it is reported that overexpression of ALDH1A1, an isozyme linked to CSCs and EMT, is related to different poor prognostic outcomes [ 38 , 39 , 40 ]. Furthermore, a secreted frizzled-related protein 1 (SFRP1) is known to be responsible for hyperplasia [ 41 ], and thus, lack of SFRP1 is accompanied by both tumor development and poor prognosis for breast cancer [ 41 ]. In our study, we found that both ALDH1A1 and SFRP1, two commonly important genes for EMT and CSCs, are capable of predicting the overall survival rates for breast cancer.…”
Section: Discussionmentioning
confidence: 99%